Disability and mothering : liminal spaces of embodied knowledge - Lewiecki-Wilson, Cynthia; Cellio, Jen (Critical perspectives on disability., 2011)
Editors Lewiecki-Wilson and Cellio have put together the first book to focus on the intersecting spaces, both cultural and personal, of disability and mothering. Derived from the Latin for threshold, the word "liminal" calls attention to the book's focus on the transitional moments and spaces where the personal and social, inside and outside, self and other converge. The volume features twenty-one previously unpublished essays by new as well as established scholars and community activists. Contributors, some of whom are themselves disabled or mothers of children with disabilities, present moving personal accounts and accessible scholarship grounded in historical study, experiential and retrospective analysis, interviews, social research, and feminist and disability studies theories